Difficult Airway Spectrum in Cats and Dogs - Management with Alternative Intubation Methods - Bektas Bilgic, Eylem (Acta Scientiae Veterinariae, 2024)
Background: Endotracheal intubation is defined as the procedure of placing a tube into the trachea. Endotracheal intubation methods include orotracheal, nasotracheal, retrograde, tracheostomy, and lateral pharyngotomy. Conditions where characteristic anatomical features obstruct the view of the vocal cords and tube placement are defined as "difficult airway”. The American Society of Anesthesiologists (ASA) defines difficult intubation as the need for 3 or more attempts to place an endotracheal tube. Conditions that can lead to upper airway obstruction include BOHS, nasopharyngeal polyps, laryngeal paralysis and tracheal collapse, temporomandibular joint diseases, and head trauma. The aim of this study was to evaluate cases causing difficult airways and the alternative orotracheal intubation methods applied for airway management. Materials, Methods & Results: The study included a total of 34 patients, 22 cats and 12 dogs, of different ages and breeds with difficult airways, brought to the Istanbul University-Cerrahpasa Faculty of Veterinary Medicine Department of Surgery Polyclinic for elective surgery. Nasotracheal intubation was performed on 10 patients where orotracheal intubation was not feasible or was deemed to obstruct the surgical field, lateral pharyngotomy on 6 patients, tracheostomy on 17 patients, and permanent tracheostomy on 2 patients. Nasotracheal intubation was applied to patients scheduled for epiglottopexy and laryngeal saccullectomy surgeries. Lateral pharyngotomy was performed for jaw locking and nasopharyngeal reconstruction surgeries. Tracheostomy was applied for mandibular osteosynthesis, jaw locking, pharyngeal tumor resection, condylectomy, zygomatic arch resection, laryngeal tumor resection, and bilateral temporomandibular joint resection. Conditions necessitating alternative intubation methods included epiglottis retroversion and laryngeal saccula eversion lesions of BOHS, maxilla and mandible fractures resulting from head trauma, symphysis mandibula separation, laryngeal stenosis, larynx and pharynx tumors, and inability to open the mouth due to malunion. Discussion: Conditions such as BOHS findings, temporomandibular joint ankylosis, laryngeal and pharyngeal lesions, oral surgery, difficult airway, and conditions leading to difficult intubation were considered. Increased fat mass in the oropharyngeal soft tissue due to obesity not only increases the risk of airway obstruction but also complicates endotracheal intubation. The difficulty in intubation experienced in cases 26 and 30, where patients were of pug breed and assessed as obese based on body condition score, supports the literature. Orotracheal intubation is a routine procedure in cats and dogs and can be easily performed. However, alternative intubation methods may be required in cases of difficult airway. The most serious consequence of the difficult airway spectrum is the inability to intubate the patient and ensure oxygenation. Laryngeal paralysis (cases 2 and 22), temporomandibular joint ankylosis (cases 6, 9, 10, 20, 21, and 33), pharyngeal (case 11) and laryngeal tumors (case 19) were considered as situations requiring urgent intervention and where orotracheal intubation was not possible. Alternative intubation methods were required in these cases, and tracheostomy was performed urgently to ensure airway patency. It was observed that alternative endotracheal intubation methods were frequently used in oral maxillofacial surgery and otolaryngology clinics to relieve the surgical field or stabilize the patient’s condition. Keywords: difficult airway, endotracheal intubation, lateral pharyngotomy, nasotracheal intubation, tracheostomy.